The Effect of Environmental Uncertainty, Budget Participation, Task Complexity on Managerial Performance Moderated by Management Accounting Information Systems - Hady, Najma Nurul; Fisher, Bobby (SENTRALISASI, 2025)
The increasing complexity and uncertainty of the business environment require organisations to optimise managerial performance in order to remain competitive. In Indonesian manufacturing companies, managerial performance is often influenced by internal and external factors such as environmental uncertainty, involvement in budget formulation, and task complexity. Although Management Accounting Information Systems (MAIS) have been widely studied in the context of decision making, their role as a moderating variable in the relationship between environmental uncertainty, budget participation, and task complexity on managerial performance has not been extensively researched. This study uses a quantitative approach with a survey method distributed to from manufacturing companies in South Jakarta. The data analysis technique used is (Moderated Regression Analysis) MRA .The results of the study indicate that Environmental uncertainty and task complexity have a significant negative effect on managerial performance, while budget participation and MAIS have a significant positive effect. MAIS was also found to weaken the negative influence of environmental uncertainty and strengthen the positive influence of budget participation on managerial performance, but it did not moderate the relationship between task complexity and managerial performance. This study introduces MAIS as a moderating variable that provides new insights into managerial performance studies. These findings emphasise the importance of implementing robust information systems to support more effective managerial strategies and decision-making.